Kajian Kampung Islam Kauman di Kecamatan Gondomanan Kota Yogyakarta - Fazri Ismail; Bambang Pranggono (UNISBA Press, 2022)
Abstract. Kampung Kauman Yogyakarta is an old residential neighborhood in the central area of ​​Yogyakarta City which has a very distinctive character, especially its Islamic historicity and religiosity. Kauman village has a pattern of settlements that gather and cluster with buildings that are close to each other so that it makes a dense area like Islamic cities in the Middle East. The reformist Islamic movement, Muhammadiyah, which was founded by KH Ahmad Dahlan was also born in Kauman Village on November 18, 1912. Although in Kauman Village there is an Islamic renewal movement and the people are obedient in carrying out Islamic teachings based on the Qur'an and Sunnah, namely anti-superstition. , heresy, Churafat (TBC) but Kauman Village is adjacent to the location of the palace's cultural tradition, namely its cultural values ​​are still mixed with mystical things. This study aims to identify Kauman Village, Yogyakarta, which can be considered as an Islamic village. This study uses a qualitative approach with the method of socio-cultural analysis of Islam and analysis of historical evidenceThis study aims to determine the socio-cultural conditions of the Kauman Islamic Village and the elements as evidence of historical heritage in Kauman Village, Yogyakarta. Data collection techniques used in this study were questionnaires, interviews, observation and literature study. The results of the research analysis show that Kampung Kauman Yogyakarta has an identity as an Islamic village as seen from the socio-cultural values ​​of its people, settlement patterns, and evidence of historical heritage elements. Abstrak. Kampung Kauman Yogyakarta merupakan sebuah lingkungan permukiman tua di kawasan pusat Kota Yogyakarta yang mempunyai karakter yang sangat khas, khususnya ciri historisitas dan religiusitas keislamannya. Kampung Kauman memiliki pola permukiman yang berkumpul dan bergerombol dengan bangunan yang saling berdempetan sehinggan menjadikan kawasan yang padat seperti kota-kota Islam di Timur Tengah. Gerakan Islam pembaharu yaitu Muhammadiyah yang didirikan KH Ahmad Dahlan juga lahir di Kampung Kauman pada tahun 18 November 1912. Meskipun di Kampung Kauman terdapat gerakan pembaharuan Islam dan masyarakatnya taat dalam menjalankan ajaran Islam yang berpedoman pada Al-Qur’an dan Sunah yakni anti dengan Tahayul, Bid’ah, Churafat (TBC) tapi Kampung Kauman berdempetan dengan lokasi tradisi budaya keraton yakni nilai kebudayaannya masih bercampur dengan hal-hal mistis. Penelitian ini bertujuan mengidentifikasi Kampung Kauman Yogyakarta dapat dianggap sebagai Kampung Islam. Penelitian ini menggunakan metode pendekatan kualitatif dengan metode analisis sosial budaya Islam dan analisis bukti sejarah untuk mengetahui kondisi sosial budaya Kampung Islam Kauman dan elemen-elemen sebagai bukti peningalan sejarah di Kampung Kauman Yogyakarta. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner, wawancara, observasi dan studi literatur. Hasil dari analisis penelitian menunjukkan bahwa Kampung Kauman Yogyakarta memiliki identitas sebagai Kampung Islam terlihat dari nilai sosial budaya masyarakatnya, pola permukiman, dan bukti elemen peninggalan sejarah.